Peran Account Executive dalam Mengatasi Klien pada Perusahaan Agency di PT Duabelas Multikreasi Indonesia - Putri Aliefiya; Dewi Winarni Susyanti (Bisnis Event, 2023)
Account Executive has an important role as client service or client-side in a company such as an agency. Not only being a liaison between the agency and client, Account Executive must be able to represent their company, and have certain skills. The purpose of this research is to know the criteria and roles of Account Executive, as well as ways to overcome obstacles to clients. This research uses qualitative methods by conducting observations, interview, and direct practice. The results of research using this method is that the author understands the criteria of a good Account Executive, the roles, and the constraints and solutions faced by Account Executive in dealing with clients and being a company representative. Keywords: Account Executive, Agency, Klien